Analysis of the Influence of Liquidity, Intellectual Capital, and Capital Structure on Financial Performance in Property Companies Listed on the Indonesia Stock Exchange - Putri Ningsih Pribadi; Wiliam Santoso; Christian Herdinata (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of liquidity, intellectual capital, and capital structure on the financial performance of property companies listed on the Indonesia Stock Exchange (IDX). The research uses a quantitative approach with financial data from property companies over a specific period. Liquidity is measured using the current ratio, intellectual capital is assessed through the Value Added Intellectual Coefficient (VAIC) method, and capital structure is evaluated using the debt-to-equity ratio. Financial performance is measured by return on assets (ROA). The data are analyzed using multiple regression analysis to determine the relationships between the variables. The findings suggest that liquidity has a positive and significant effect on financial performance, while intellectual capital and capital structure show mixed results, with intellectual capital having a significant positive impact and capital structure showing no significant effect. These results highlight the importance of liquidity management and intellectual capital in enhancing financial performance in the property sector. The study provides valuable insights for property companies and investors, emphasizing the need for efficient capital management and leveraging intellectual assets to improve profitability and competitiveness in the market.